2019
DOI: 10.1055/s-0039-1695713
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Head and Neck Mucormycosis: A Literature Review and Own Experience in Immediate Reconstruction

Abstract: Background Mucormycosis is a rare invasive and fatal fungal infection. A prompt diagnosis is the most critical aspect for an improved patient outcome. Along with antifungal therapy, radical surgical debridement must be done expeditiously to eradicate this fungus. In this article, we evaluated the feasibility of immediate reconstruction after surgical debridement. Methods A retrospective study was performed at Hospital Regional de Alta Especialidad de Ixtapaluca, Estado de México, Mexico, between Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Zygomatic implants have emerged as a successful entity in such cases [206]. Various authors have reported use of osteo-cutaneous free flaps like free fibula flap, radial forearm, and deep circumflex iliac artery flap with successful uptake [203,207].…”
Section: Maxillectomy/palatal Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zygomatic implants have emerged as a successful entity in such cases [206]. Various authors have reported use of osteo-cutaneous free flaps like free fibula flap, radial forearm, and deep circumflex iliac artery flap with successful uptake [203,207].…”
Section: Maxillectomy/palatal Resectionmentioning
confidence: 99%
“…Facial, nasal, and oral deformities are known complications of the surgical management of ROCM [218]. These resultant defects require reconstruction in the form of loco-regional or distant flaps with or without prosthesis for dental and palatal defects [207].…”
Section: Complications Of Surgical Treatmentmentioning
confidence: 99%
“…20 Some authors have also reported multiple debridement sessions to gain disease control and delayed reconstruction. 21,22 In comparison to most of the studies reported in literature in which reconstructions of almost (88%) all published head and neck mucormycosis cases are performed secondarily, 23 in our study, we postulate extensive wide tissue resection and immediate reconstruction as an adequate treatment option for patients with ROC mucormycosis to decrease further operations and improve recovery. Even though an additional revision procedure is required to restore cosmesis, autologous reconstruction ensures adequate coverage of the defect, all the while supporting the facial contour.…”
Section: Discussionmentioning
confidence: 53%
“…It is vital to provide these patients with a good outcome in terms of survival, quality of life, speech, feeding and aesthetics [7]. The appropriate technique for reconstruction depends primarily on the type of anatomical defect.…”
Section: Discussionmentioning
confidence: 99%